Characterization of bovine and ovine basal-out and apical-out ileum organoids - Ambre F. Chapuis; Tanith Harte; Daniel R. G. Price; Marc N. Faber; William M. Anderson; Barbara Shih; Jayne C. Hope; Jo Moore; David Smith (Royal Society Open Science, 2025)
Organoids are three-dimensional stem cell-derived structures that differentiate into multiple cell types. Their capacity to self-organize, coupled with the presence of diverse cell types, means that organoids resemble their organ of origin in architecture and function. Organoids from intestinal tissues have been extensively used as a three-dimensional model for in vitro studies of the gut. However, they typically self-organize with basal-out polarity when cultured in a three-dimensional extracellular matrix scaffold, presenting a hurdle for experiments that require access to the apical epithelial surface. Methods to invert the surface polarity of intestinal organoids have been reported, but little information exists on how this change of polarity impacts gene expression and cell populations present within the organoids. To address this knowledge gap, we modelled both polarity states in intestinal organoids from two different ruminant species. Apical-out organoids largely retained the same gene expression profile as basal-out organoids. Moreover, a combination of RNA-seq and immunohistochemistry analyses demonstrated the retention of specific markers of enterocytes, enteroendocrine, goblet and tuft cells present in organoids of both polarity states. This study presents a comprehensive validation of apical-out ileal organoids, providing supporting evidence for the utility of this model in experiments that require access to the apical surface.